The Level of Economic Development and the Impact of Financial Structure on Economic Growth: Evidence from Dynamic Panel Data Analysis - Zukarnain Zakaria (Asian Academy of Management Journal of Accounting and Finance, 2007)
The objective of this paper is to examine the impact of financial structure on economic growth and also to investigate whether the impacts are different between countries with difference levels of income; low- and middle-income countries, and high-income countries. This paper uses a panel data approach and include 44 countries. The Generalised Method of Moments (GMM) system approach has been used in estimation process. The findings from the estimation suggest that to have more developed stock markets relative to the banking sector will promote better growth in high-income countries but not in the low- and middle-income countries. This paper also finds strong evidence that the effect of financial structure on investment depends on the level of income of the country.